Spain's war of independence : President Azaą ... put the case of the Spanish Republic before the world / Azaą ... [et al.] ; [prol. Fernando de los Ríos] - Azaą, Manuel (1880-1940) Negrín, Juan (1892-1956) Prieto, Indalecio (1883-1962) Álvarez del Vayo, Julio (1891-1975) Martínez Barrio, Diego (1883-1962) Portela Valladares, Manuel (1867-1952) Ríos Urruti, Fernando de los (1879-1949)
Contiene discursos de: Manuel Azaą, Juan Negrín, Indalecio Prieto, Julio Alvarez del Vayo, Diego Martínez Barrio y Manuel Portela Valladares